2021
DOI: 10.1097/01.aoa.0000766136.99428.89
|View full text |Cite
|
Sign up to set email alerts
|

Antenatal Dexamethasone for Early Preterm Birth in Low-resource Countries

Abstract: The members of the writing committee assume responsibility for the overall content and integrity of this article. The full names, academic degrees, and affiliations of the members of the writing committee are listed in the Appendix.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…likely term born). Reassuringly however, a subsequent large randomised control trial of 2852 women at risk of early preterm birth (26 +0 to 33 + 6 weeks’ gestation) attending sites with maternal and neonatal hospital services meeting the WHO criteria for antenatal corticosteroid treatment in five low and middle income countries, found that, compared to placebo, dexamethasone phosphate reduced neonatal death (RR 0.84; 95% CI 0.72–0.97; P = 0.03) and perinatal mortality (RR 0.88; 95% CI 0.78–0.99; P = 0.04) without increasing maternal infection (RR, 0.76; 95% CI 0.56–1.03) 60 Evidence level 1– …”
Section: What Are the Risks Associated With The Administration Of Ant...mentioning
confidence: 99%
See 1 more Smart Citation
“…likely term born). Reassuringly however, a subsequent large randomised control trial of 2852 women at risk of early preterm birth (26 +0 to 33 + 6 weeks’ gestation) attending sites with maternal and neonatal hospital services meeting the WHO criteria for antenatal corticosteroid treatment in five low and middle income countries, found that, compared to placebo, dexamethasone phosphate reduced neonatal death (RR 0.84; 95% CI 0.72–0.97; P = 0.03) and perinatal mortality (RR 0.88; 95% CI 0.78–0.99; P = 0.04) without increasing maternal infection (RR, 0.76; 95% CI 0.56–1.03) 60 Evidence level 1– …”
Section: What Are the Risks Associated With The Administration Of Ant...mentioning
confidence: 99%
“…9 Although the majority of data within the meta-analysis was from high income settings, the meta-analysis did include data from a large randomised control trial of 2852 women at risk of early preterm birth (26 +0 to 33 +6 weeks' gestation) at sites with maternal and neonatal hospital services meeting the WHO criteria for antenatal corticosteroid treatment in five low and middle income countries. 60 Evidence level 1+…”
mentioning
confidence: 99%
“…9 Women and neonates were recruited from 29 secondary-level and tertiary-level hospitals: six in Bangladesh, four in India, four in Kenya, 13 in Nigeria, and two in Pakistan. 10 Hospitals were eligible to partici pate if they could reasonably meet the WHO criteria for antenatal dexamethasone administration. 9 The full protocol has been published with main findings separately.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, a multicentre study in five low-resource countries demonstrated that the administration of ACS to women who were at risk for early preterm birth reduced the incidences of neonatal death and stillbirth or neonatal death without increasing the incidence of maternal bacterial infection. 2 Regarding late preterm infants, the administration of ACS at 34 + 0 to 36 + 6 weeks of gestation has been shown to reduce respiratory morbidity. 3 The evidence for this was mainly dominated by the Antenatal Late Preterm Steroids Trial (ALPS), which was conducted in tertiary hospitals in the United States with a high standard of care provided to preterm infants and their mothers.…”
Section: Commentarymentioning
confidence: 99%
“…The evidence for these benefits is based on studies conducted largely in high‐resource countries. Recently, a multicentre study in five low‐resource countries demonstrated that the administration of ACS to women who were at risk for early preterm birth reduced the incidences of neonatal death and stillbirth or neonatal death without increasing the incidence of maternal bacterial infection 2 . Regarding late preterm infants, the administration of ACS at 34 + 0 to 36 + 6 weeks of gestation has been shown to reduce respiratory morbidity 3 .…”
Section: Commentarymentioning
confidence: 99%